2019
DOI: 10.3389/fchem.2019.00156
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol to Glyceraldehyde Oxidation Reaction Over Pt-Based Catalysts Under Base-Free Conditions

Abstract: Glycerol valorization through partial oxidation is a good way of obtaining many different molecules with high added value such as glyceric acid, tartronic acid, dihydroxyacetone, etc. Among the potential products, glyceraldehyde is an interesting chemical compound for its various applications in different domains such as organic chemistry, medical, and cosmetic industries. In the present paper, we studied the effect of different supports on the glycerol oxidation reaction in a batch reactor applying base-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
0
23
1
1
Order By: Relevance
“…Usually, it was observed a low conversion combined with a high selectivity or high conversion together with low selectivity. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Recently, Liu et al 40 reported the photoelectrochemical oxidation of 1,3-DHA directly from glycerol using nanoporous BiVO 4 , with high conversion and selectivity of 51%. However, side products such as glyceric acid, formic acid, glycolic acid, CO 2 , CO and H 2 O 2 and O 2 were observed.…”
Section: Expeditious Syntheses To Pharmochemicals 13-dihydroxyacetonmentioning
confidence: 99%
“…Usually, it was observed a low conversion combined with a high selectivity or high conversion together with low selectivity. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Recently, Liu et al 40 reported the photoelectrochemical oxidation of 1,3-DHA directly from glycerol using nanoporous BiVO 4 , with high conversion and selectivity of 51%. However, side products such as glyceric acid, formic acid, glycolic acid, CO 2 , CO and H 2 O 2 and O 2 were observed.…”
Section: Expeditious Syntheses To Pharmochemicals 13-dihydroxyacetonmentioning
confidence: 99%
“…There is thus an increasing surplus of glycerol, creating a need to develop alternative ways to use residual glycerol. 2 Due to its high functionalization, glycerol can be transformed into several value-added products ( Table 1), such as lactic acid, [3][4][5] glyceric acid, 6-8 glycolic acid, [9][10][11] oxalic acid, 9,12 dihydroxyacetone, [13][14][15] glyceraldehyde, [16][17][18] 1,2-propanediol, [19][20][21] 1,3-propanediol, 22-24 1-propanol, 25,26 acrylic acid, [27][28][29] acrolein, [30][31][32] syngas, [33][34][35] mono-, di-, tri-glycerides, [36][37][38] triacetin, [39][40][41] glycerol oligomers, 42,43 and polymers. 44 Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry 45,46 as raw material for the production of pharmaceuticals, 47 cosmetics, 48 textiles, 49 leather,…”
Section: Reactionmentioning
confidence: 99%
“…Due to its high functionalization, glycerol can be transformed into several value‐added products (Table ), such as lactic acid, glyceric acid, glycolic acid, oxalic acid, dihydroxyacetone, glyceraldehyde, 1,2‐propanediol, 1,3‐propanediol, 1‐propanol, acrylic acid, acrolein, syngas, mono‐, di‐, tri‐glycerides, triacetin, glycerol oligomers, and polymers . Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry as raw material for the production of pharmaceuticals, cosmetics, textiles, leather, and, in a fast‐growing niche market, as monomer for the biodegradable polymer poly‐(lactic acid) or PLA .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 According to the US Department of Energy, glycerol has been classified as one of the 12 building block chemicals obtained from biomass derived platform molecules, which can be utilised to produce high value-added biomass-based chemicals. 12 Many potential reactions such as dehydration, 13 oxidation, 14 esterification 15 and hydrogenolysis 16 were reported in the literature as promising routes for glycerol valorisation. The valorisation of glycerol is not solely about improving the economic competition of biodiesel but also contributing to the environmentally sustainable “waste to wealth” concept.…”
Section: Introductionmentioning
confidence: 99%